2008
DOI: 10.1016/j.aca.2008.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Improving CMC-derivatization of pseudouridine in RNA for mass spectrometric detection

Abstract: A protocol that utilizes matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) and N-cyclohexyl-N′-β-(4-methylmorpholinium)ethylcarbodiimide (CMC) derivatization to detect the post-transcriptionally modified nucleoside, pseudouridine, in RNA has been optimized for RNase digests. Because pseudouridine is mass-silent (i.e. the mass of pseudouridine is the same as the mass of uridine), after CMC derivatization and alkaline treatment, all pseudouridine residues exhibit a mass shift of 252 Da t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 28 publications
0
44
1
Order By: Relevance
“…However, the mass of detected product ions shifted to two carbodiimide units from c 9 (m/z 1687.7 3 m/z 1813.3) onward and y 8 (m/z 1429.0 3 m/z 1554.6) onward (supplemental Table S1. These data are in contrast with a previous finding (28) where RNase A and snake venom phosphodiesterase-digested tRNA Tyr was analyzed by matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) after CMCT derivatization. Those earlier data also showed that two carbodiimide units were added to the anticodon region of tRNA Tyr .…”
Section: Lc-ms/ms Analysis Of Rnase T1 Digest Of E Coli Trna Tyr -contrasting
confidence: 53%
See 4 more Smart Citations
“…However, the mass of detected product ions shifted to two carbodiimide units from c 9 (m/z 1687.7 3 m/z 1813.3) onward and y 8 (m/z 1429.0 3 m/z 1554.6) onward (supplemental Table S1. These data are in contrast with a previous finding (28) where RNase A and snake venom phosphodiesterase-digested tRNA Tyr was analyzed by matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) after CMCT derivatization. Those earlier data also showed that two carbodiimide units were added to the anticodon region of tRNA Tyr .…”
Section: Lc-ms/ms Analysis Of Rnase T1 Digest Of E Coli Trna Tyr -contrasting
confidence: 53%
“…Prior reports discussed the possibility of an additional pseudouridine (31) or off-target derivatization (28), but until now, those possibilities remained uninvestigated. To clarify this open question, we conducted an exhaustive examination of E. coli tRNA Tyr using multiple pseudouridine detection strategies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations